2017
DOI: 10.3390/biomedicines5020017
|View full text |Cite
|
Sign up to set email alerts
|

Coconut (Cocos nucifera) Ethanolic Leaf Extract Reduces Amyloid-β (1-42) Aggregation and Paralysis Prevalence in Transgenic Caenorhabditis elegans Independently of Free Radical Scavenging and Acetylcholinesterase Inhibition

Abstract: Virgin coconut oil (VCO) has been the subject of several studies which have aimed to alleviate Alzheimer’s disease (AD) pathology, focusing on in vitro antioxidant and acetylcholinesterase (AChE) inhibitory activities. Here, we studied an underutilized and lesser-valued part of the coconut tree, specifically the leaves, using in vitro and in vivo approaches. Coconut leaf extract (CLE) was screened for antioxidant and AChE inhibitory properties in vitro and therapeutic effects in two strains of transgenic Caeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…AD is a prevalent disease that affects more than 26 million people globally, and is the most common neurodegenerative disease worldwide [ 7 ]. AChE inhibitors (AChEIs) have medical applications and are particularly important for the symptomatic treatment of Alzheimer’s disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…AD is a prevalent disease that affects more than 26 million people globally, and is the most common neurodegenerative disease worldwide [ 7 ]. AChE inhibitors (AChEIs) have medical applications and are particularly important for the symptomatic treatment of Alzheimer’s disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different products from the coconut plant have been studied extensively for their medicinal properties (Roopan 2016). Research has demonstrated the presence of metabolites such as polyphenols, glycosides, steroids, alkaloids, terpenoids, and others which could be responsible for those activities (Renjith et al 2013;Manalo et al 2017;Oliveira et al 2009;Singla et al 2011;Soumya et al 2014). More specifically, the husk extracts of C. nucifera have shown to have antimalarial properties when tested in vitro and in vivo (Adebayo et al 2012;Adebayo et al 2013;Balogun et al 2014;Angeles et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the traditional use of C. nucifera husk, water and inflorescence on mice and rats to address several pathologies (Naskar et al 2011;Rinaldi et al 2009;Renjith et al 2013;Alviano et al 2004;Omoboyowa et al 2016). One study describes the use of C. nucifera leaf extracts as reducing amyloid-b aggregation in transgenic Caenorhabditis elegans (Manalo et al 2017). Another study describes the safety of C. nucifera leaf extracts in mice, however, it does not evaluate the effectiveness of these extracts on any pathology (Paul et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has traditionally been used in countries of South Asia, Africa, and America, for treating arthritis, diarrhea, fevers, inflammation, skin infections, miscarriage prevention, asthma, female sterility and as a diuretic, among others[2]. A leaf extract from the coconut plant decreases amyloid-β 1–42 aggregation and paralysis[3]. Catechins and epicatechins were responsible for the antiparasitic activity from the husk of Cocos nucifera against Leishmania parasites[4].…”
Section: Introductionmentioning
confidence: 99%